Conditioning of Norway spruce (Picea abies (L.) Karst.) Sowing Material - Szajsner, Hanna; Koszelnik-Leszek, Anna; Błasiak, Karolina (Polish Journal of Natural Sciences, 2023)
Norway spruce (Picea abies (L.) Karst.) is a relatively demanding species compared to other conifers. It is therefore important to provide it with optimal growth conditions in the early stages of development. The laboratory and pot experiments were carried out on seed material of 10 different genotypes of Norway spruce bio-stimulated with semiconductor laser light. The following variants were used: control without irradiation (C) and multiplied dose variants (0,25 × 10-2 J/cm2), three-fold (D3), six-fold (D6), and nine-fold (D9). Morphological features, fresh and dry weight of seedlings and the content of photosynthetically active pigments were assessed. Under the influence of the applied radiation, morphological features of seedlings were stimulated, and dose D6 turned out to be the most effective. It caused the stimulation of the tested features both in the experiment conducted in laboratory conditions and in a tunnel. The application of doses D3 and D9 caused an increase in chlorophyll content.